Israel Literacy: Cultivating Literacy and Critical Thinking about Israel within Jewish and Israel Education. Issue 1 (2nd January 2023) - Fish, Rachel
ABSTRACT: This paper reviews the taxonomies and characteristics of Israel education articulated by Benji Davis and Dr. Hanan Alexander while suggesting that their specific educational philosophy, Mature Zionism, ought not be siloed only to educating about Israel but rather extended to Jewish education writ large. Developing a framework of Israel literacy provides an opportunity for Israel educators to develop skills and knowledge about Israel while applying it to the context of Israeli history and society. Futhermore, this paper proposes reclaiming the ethnos identity of Jews, as a tribe or a people, allowing for this concept to be integrated more fluidly within Jewish educational contexts.